2020
DOI: 10.3892/etm.2020.9447
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of infliximab in the treatment of Kawasaki disease: A systematic review and meta‑analysis

Abstract: The present study aimed to review the relevant studies in order to determine the efficacy of infliximab (IFX) in the treatment of Kawasaki disease (KD). The relevant studies were retrieved using the PubMed, Cochrane and Embase databases. Key sources in the literature were reviewed; all articles published by July 2019 were considered for inclusion. For each study, odds ratios, mean difference and 95% confidence interval (95% CI) were assessed to evaluate study outcomes. A total of 16 studies involving 429 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Pooled data from 16 studies involving 429 patients was analysed, with infliximab treatment causing less complications such as fever, mucosal lesions and lymphadenopathy in the cervical region as compared to traditional immunoglobulin treatment. Laboratory results also showed more significant improvement in platelet count and inflammatory markers such as C-reactive protein and white cell counts in the infliximab groups as compared to the immunoglobulin groups [15]. Similar benefits were noted in groups receiving combination therapy with infliximab and immunoglobulins, further supporting the potential benefit of infliximab in KD treatment [16].…”
Section: Management and Outcomesmentioning
confidence: 52%
See 1 more Smart Citation
“…Pooled data from 16 studies involving 429 patients was analysed, with infliximab treatment causing less complications such as fever, mucosal lesions and lymphadenopathy in the cervical region as compared to traditional immunoglobulin treatment. Laboratory results also showed more significant improvement in platelet count and inflammatory markers such as C-reactive protein and white cell counts in the infliximab groups as compared to the immunoglobulin groups [15]. Similar benefits were noted in groups receiving combination therapy with infliximab and immunoglobulins, further supporting the potential benefit of infliximab in KD treatment [16].…”
Section: Management and Outcomesmentioning
confidence: 52%
“…Tumor necrosis factor-alpha (TNF-α) levels are raised more significantly in KD patients who develop coronary artery aneurysms as compared to those without. This could be related to TNF-α triggering the release of chemokines by endothelial cells, increasing permeability of the endothelial lining to other inflammatory cells such as neutrophils, causing more severe damage to the affected arteries [15].…”
Section: Pathogenesis and Complicationsmentioning
confidence: 99%
“… 29 IFX is a vital pro-inflammatory factor significantly elevated in the blood circulation of children with KD. 30 The effectiveness of IFX in combination with IVIG treatment of nonreactive type KD is controversial. A retrospective review of 2 centers suggested that patients receiving infliximab had shorter hospitalization and fewer days of fever.…”
Section: Discussionmentioning
confidence: 99%
“…40,43 Otros estudios previos ya había dado resultados parecidos. 44,45 Glucocorticoides Un metaanálisis que incluyó 19 estudios observó una reducción significativa de AAC cuando los corticosteroides se utilizaron como tratamiento de primera línea sumado a la IGIV. Curiosamente, el análisis de subgrupos por etnicidad mostró que la reducción del riesgo fue estadísticamente significativa en la población japonesa, pero no en los no japoneses.…”
Section: Infliximabunclassified